2002
DOI: 10.1021/cm011175q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Thin Films of Cadmium Oxide

Abstract: The Cd(C 5 F 6 HO 2 ) 2 ‚2H 2 O complex was investigated by X-ray crystallography, mass spectroscopy, 1 H NMR spectroscopy, TG-DTG thermal measurements, and infrared transmittance spectroscopy. X-ray single-crystal data show that the cadmium ion is chelated by the oxygens of the hfa anion ligand and bound to the oxygens of two cis-disposed water molecules. Deposition experiments, in a low-pressure horizontal hot-wall reactor, on optically transparent SiO 2 substrates using the above complex result in CdO films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 41 publications
10
62
0
Order By: Relevance
“…3(D) shows the O(1s) core-levels for CdSe systems with precursor Cd/Se ratio varying from 0.5:1 to 3:1, respectively. The broad O(1s) peak for CdSe-0.5:1-3:1 systems has been deconvoluted into main peaks at $532 eV corresponding to TOPO, 530 and 534 eV corresponding to Se-and Cd-related oxides [26,27]. With increase in Cd/Se ratio from 0.5:1 to 2:1, XPS O1s core-level intensity of peaks at 532 eV is enhanced, thus signifying the increased contribution of TOP/TOPO groups in passivating CdSe nanocrystallites.…”
Section: Resultsmentioning
confidence: 99%
“…3(D) shows the O(1s) core-levels for CdSe systems with precursor Cd/Se ratio varying from 0.5:1 to 3:1, respectively. The broad O(1s) peak for CdSe-0.5:1-3:1 systems has been deconvoluted into main peaks at $532 eV corresponding to TOPO, 530 and 534 eV corresponding to Se-and Cd-related oxides [26,27]. With increase in Cd/Se ratio from 0.5:1 to 2:1, XPS O1s core-level intensity of peaks at 532 eV is enhanced, thus signifying the increased contribution of TOP/TOPO groups in passivating CdSe nanocrystallites.…”
Section: Resultsmentioning
confidence: 99%
“…Some examples of this are: Gulino et al [10] [12].Uplane et al [13] reported the preparation of CdO thin films onto the hot glass substrate at 400˚C by spray pyrolysis of the aqueous cadmium acetate solution. Varkey and Fort [14] prepared transparent CdO thin films on glass substrate using the aqueous solution of soluble cadmium amine complexes as a precursor of CdO.…”
Section: Introductionmentioning
confidence: 99%
“…We are, however Its attractive characteristics include a straightforward, onestep aqueous synthesis under ambient conditions from commercially available starting materials, excellent volatility, as well as excellent air and thermal stability. Further advances in cadmium precursor technology by our laboratory, [24] and the complementary approaches of other groups, [25] have resulted in an increased film growth capability for discovery, synthesis, and optimization of cadmium-containing opto-electronic materials. In this contribution, we report the first growth of transparent conducting Cd 2 SnO 4 films by a MOCVD process.…”
mentioning
confidence: 99%